Paeonol Inhibits Migration, Invasion and Bone Adhesion of Small Cell Lung Cancer Cells - Tian, Yong; Chen, Cong; Zhang, Yu; Zhang, Zhen; Xie, Haiyan (Current Signal Transduction Therapy, 2015)
Objective: Bone is one of the most common sites of metastases in human small cell lung cancer (SCLC) which is often associated with skeletal-related events and poor prognosis. To explore the significance of Paeonol (Pae) in SCLC, we hypothesize that Pae can inhibit cell proliferation, migration and invasion, finally inhibit bone metastases of SCLC. Methods: The effects of Pae on proliferation of SCLC were detected by MTT assay in vitro. The effects of Pae on migration and invasion of SCLC were detected by Transwell assay in vitro. Furthermore, bone chip adhesion assay was used to explore the effects of Pae on the strength of bone adhesion and metastatic ability in SCLC cell line. Results: MTT results showed that Pae suppressed SCLC cell proliferation in a dose-dependent manner. Transwell assay results showed Pae suppressed SCLC cell migration and invasion in a dose-dependent manner. Furthermore, the cells treated by Pae showed decreased ability of bone adhesion and bone metastases in vitro compared with control. Conclusions: The study indicated Pae could suppress bone metastases of SCLC cells and Pae might be a promising medicine for therapy of SCLC bone metastases.
Keywords: Bone metastases